Utilisation of eye care services in Shah Alam population / Nurzawani Abd Rahim - Abd Rahim, Nurzawani (2016)
Background: Eye care services were introduced to reduce the amount of visual impairment by ensuring a good healthy vision. The role of eye care service is not only to treat the people with symptoms, but it is also for reventive measures and to check on the general health of their eyes even without the symptoms. Several studies have been done in several countries to determine the utilization of the eye care services and the influencing factors. However, no similar studies have been conducted in Malaysia. Aim: The objective of this study is to determine the level of awareness on availability of eye care services among Shah Alam residents, to investigate factors and barriers related to the use of optometry services among Shah Alam community, and to identify the association between the awareness of Optometry services with the level of utilisation of the optometry services. Method: The study is conducted by using a printed form questionnaire with closed ended questions that were distributed to random participants selected in Shah Alam. A random sampling method is used in this study. Result: There is a high level of awareness on the availability of eye care services among Shah Alam residents. Unaffordable cost of treatment and unknown benefit of eye care services and unwillingness to go for eye examination without vision changes are factors affecting the utilisation of eye care services. There is low association between the awareness of eye care services and the level of utilisation. Conclusion: The presence of a service alone is not sufficient to ensure its utilization. This study has helped to identify groups that need information, encouragement, or assistance to utilize existing services. In the future, similar study should be done, including the different level of education and socioeconomic income among the participants.